A novel and efficient surgical procedure for pyriform sinus fistulas in children - Chen, Jiarui; Wang, Ying; Shen, Chenling; Wang, Jing; Li, Xiaoyan (Frontiers in Pediatrics, 2024)
Objective: To evaluate the efficacy of a novel surgical procedure for piriform sinus fistulas in children via the external cervical approach through hypopharynx.A retrospective analysis was conducted on 71 pediatric patients with Pyriform sinus fistula (PSF) who were treated at Department of Otolaryngology Head and Neck Surgery, Shanghai Children's Hospital, from 2012 July to 2022 July. Surgical treatment of PSF was performed via the external cervical approach through the hypopharynx with dye instilled through the internal opening to serve as a guide for identifying the tract.Results: All the internal orifices were found in piriform sinus by direct laryngoscopy in all 71 cases under general anesthesia. Two cases had a postoperative temporary hoarseness and the hoarseness returned to normal after three months. The other patients had no complications such as parapharyngeal abscess and incision infection. All patients were followed up for 23 months to 70 months，and no recurrence was found.The novel surgical procedure of PSF performed via hypopharynx was with advantages such as short operation path, quick recovery, less complications and low recurrence rate. It is a better choice in management for recurrence cases after repeated cauterization endoscopic surgery， patients with visible cervical surgical scar， and patients with visible mass.